2015
DOI: 10.1016/j.jbiotec.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Inverse problem analysis of pluripotent stem cell aggregation dynamics in stirred-suspension cultures

Abstract: The cultivation of stem cells as aggregates in scalable bioreactor cultures is an appealing modality for the large-scale manufacturing of stem cell products. Aggregation phenomena are central to such bioprocesses affecting the viability, proliferation and differentiation trajectory of stem cells but a quantitative framework is currently lacking. A population balance equation (PBE) model was used to describe the temporal evolution of the embryonic stem cell (ESC) cluster size distribution by considering collisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Moreover, the same group showed that the aggregation kernel representing aggregation dynamics used in PBE models can be derived from experimental size distributions of cultured ESC clusters as a solution of the inverse problem. 42 Their results revealed that the rate of change of the average aggregate size depends on agitation rates and peaks at the intermediate rate. This analytical framework can be used to derive insights about the cell clustering processes of specific cell types.…”
Section: Models For Describing Aggregate Populations By Sizementioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the same group showed that the aggregation kernel representing aggregation dynamics used in PBE models can be derived from experimental size distributions of cultured ESC clusters as a solution of the inverse problem. 42 Their results revealed that the rate of change of the average aggregate size depends on agitation rates and peaks at the intermediate rate. This analytical framework can be used to derive insights about the cell clustering processes of specific cell types.…”
Section: Models For Describing Aggregate Populations By Sizementioning
confidence: 98%
“…Using a similar strategy implemented for aggregation of platelets, Kehoe et al, applied a mass‐structured population balance equation (PBE) to model the distribution of mESC aggregate sizes in stirred‐tank bioreactors; the prediction made with this model was consistent with experimentally obtained data. Moreover, the same group showed that the aggregation kernel representing aggregation dynamics used in PBE models can be derived from experimental size distributions of cultured ESC clusters as a solution of the inverse problem . Their results revealed that the rate of change of the average aggregate size depends on agitation rates and peaks at the intermediate rate.…”
Section: Modeling Human Pluripotent Stem Cell Expansion Processesmentioning
confidence: 99%
“…Finally, suspension culture of 3D cell aggregates may offer a potential scalable solution to stem cell manufacturing, as there is low cost of goods and high cell yields ( Hookway et al., 2016 ). However, 3D aggregate suspensions require high shear rates in stir-tank reactors to prevent cell agglomeration, affecting cell viability, and differentiation ( Rostami et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of aggregation kernels was demonstrated by Wright and Ramkrishna (1992), based on the assumption of self-similarity. The latter approach was subsequently used by other groups for determining kernels for stem cell aggregation (Rostami et al, 2015) and sludge flocculation (Torfs et al, 2012). The self-similarity of the particle size distribution depends on the aggregation kernel as well as on the initial conditions and may not be achieved under conditions where aggregation and growth occur simultaneously, as for instance reported by Bramley et al (1997).…”
Section: Introductionmentioning
confidence: 99%